Evaluating the Investment Facilitation Policy in Boyolali Regency: An Analysis of Inputs, Processes, Outputs, and Outcomes - Yousy Fernanda Ayu Albela; Ida Hayu Dwimawanti (Jurnal Administrasi dan Kebijakan Publik, 2025)
This study evaluates the effectiveness of the investment facilitation policy in Boyolali Regency to determine the extent to which it has achieved its intended goals and to identify the main implementation challenges. Using a descriptive qualitative case study approach, data were collected through in-depth interviews, field observations, and document analysis. The policy evaluation focuses on four aspects of policy performance: input, process, output, and outcome. The findings indicate that although policy outputs generally align with the established targets, several weaknesses persist, particularly in the quality and capacity of human resources, the condition of supporting road infrastructure, and the consistency of communication between the government and investors. These weaknesses limit the overall impact of the investment facilitation policy on regional investment growth. The study concludes that strengthening institutional capacity and improving policy socialization are essential to enhance policy effectiveness. This research contributes to the broader literature on local investment governance by providing empirical insights into the barriers that hinder effective policy implementation at the subnational level.